UPAYA PENGGUNAAN PERANGKAT MULTIMEDIA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA-SISWI KELAS VIII PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH TSANAWIYAH AL-MU’IN KOTA TANGERANG - Ajiz Guntur (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2021)
ABSTRACTThe problem raised in this study is how to use multimedia tools to increase student motivation in class VIII MTs Al Mu'in Tangerang City in the subject of Islamic cultural history. While the purpose of this study is to find out how to use multimedia devices, choose multimedia devices, and assess the effectiveness of using multimedia devices in the learning process, related to school efforts in increasing the learning motivation of students in the classroom. The method used in this research is to use the observation method, interview method, and documentation method. Meanwhile, to analyze the results of this study, qualitative descriptive analysis is used which consists of three activities, namely data collection as well as data reduction, data presentation and conclusions or verification. It is known that the use of multimedia devices at Mts Al-Mu'in Tangerang City in increasing learning motivation is by means of teachers using and combining methods of lectures, discussions, and the use of multimedia devices in the form of projectors, videos, and visual media even though the use of multimedia devices at MTs Al -Mu'in at this point is not so significant because of the limitations of the multimedia device itself.